(untitled) (Journal of Economic Research & Business Administration, 2019)
The article discusses the stages of the formation of a national financial management system. In Kazakhstan, the beginning of corporatization and privatization on a large scale, the growth in the number of newly established private companies, the expansion of contacts with foreign partners, including in the area of investment operations, require urgent monitoring of modern mechanisms and methods of financial management, the complex process of managing financial resources of a company engaged in business. activities, although some elements of financial management were present at different stages of economic development, but in the full sense of this understanding tons in financial management was not implemented. According to the author of the article, the transition to market relations has led to the separation of financial management functions at the state level and financial relations to self-regulation within commercial organizations, which creates the official basis for the implementation of financial management. From the point of view of the author, financial methods and tools, the functioning of financial management available for the relationship, the process analyzed in literature and adaptation used in the practice of taking into account Kazakhstan, are not considered in the complex because of the overall result of managing the organizational staff of the system.